Toward New Modalities in VEP-Based BCI Applications Using Dynamical Stimuli: Introducing Quasi-Periodic and Chaotic VEP-Based BCI - Shirzhiyan, Zahra; Keihani, Ahmadreza; Farahi, Morteza; Shamsi, Elham; GolMohammadi, Mina; Mahnam, Amin; Haidari, Mohsen Reza; Jafari, Amir Homayoun (Frontiers in Neuroscience, 2020)
Visual Evoked potentials (VEP) to periodic stimuli are commonly used in brain computer interfaces for their favorable properties such as high target identification accuracy, less training time and low surrounding target interference. Conventional periodic stimuli can lead to subjective visual fatigue due to continuous and high contrast stimulation. In this study, we compared quasi-periodic and chaotic complex stimuli to common periodic stimuli for use with VEP-based BCI. Canonical Correlation Analysis (CCA) and coherence methods were used to evaluate the performance of the three stimulus groups. Subjective fatigue caused by the presented stimuli was evaluated by Visual Analogue Scale (VAS). Using CCA with M2 template approach, target identification accuracy was highest for the chaotic stimuli (M=86.8, SE=1.8) compared to the quasi periodic (M=78.1, SE=2.6, p = 0.008) and periodic stimuli groups (M=64.3, SE=1.9, p = 0.0001). The evaluation of fatigue rates revealed that the chaotic stimuli caused less fatigue compared to the quasi-periodic (p = 0.001) and periodic stimuli groups (p = 0.0001). In addition, the quasi-periodic stimuli led to lower fatigue rates compared to the periodic stimuli (p = 0.011). We conclude that the target identification results were better for the chaotic group compared to the other two stimuli groups with CCA. In addition, the chaotic stimuli led to lesser subjective visual fatigue compared to the periodic and quasi periodic stimuli and can be suitable for designing new comfortable VEP-based BCIs.